2015
DOI: 10.1167/iovs.15-17208
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Early-Stage Glaucoma by Grid-Wise Macular Inner Retinal Layer Thickness Measurement and Effect of Compensation of Disc-Fovea Inclination

Abstract: Grid-wise analysis of macular GCC--especially using 8 × 8 grids and normative data-based cutoff values--was very useful for diagnosing early-stage glaucoma, though compensation of the disc-fovea inclination had little effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
2
17
2
2
Order By: Relevance
“…In the current study, although the simply summed values of measurements were used, AUC-ROC was 0.972, which was comparable to that reported by Yoshida et al9 However, these studies8,9 were conducted in hospital-based case–control settings. In contrast, we created a reasonable study algorithm in a population-based case–control setting and then applied that to a population-based setting; in the latter setting, the glaucoma positive rate was 16.3%, which seemed remarkably high.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the current study, although the simply summed values of measurements were used, AUC-ROC was 0.972, which was comparable to that reported by Yoshida et al9 However, these studies8,9 were conducted in hospital-based case–control settings. In contrast, we created a reasonable study algorithm in a population-based case–control setting and then applied that to a population-based setting; in the latter setting, the glaucoma positive rate was 16.3%, which seemed remarkably high.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, we created a reasonable study algorithm in a population-based case–control setting and then applied that to a population-based setting; in the latter setting, the glaucoma positive rate was 16.3%, which seemed remarkably high. In addition, we applied the protocol used by Mayama et al8 to our study population (5,208 subjects; mean age, 48 years). In the Mayama et al study,8 the glaucoma positive rate was 13.3% (694 subjects; Nakano, unpublished data, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,47 While a number of past studies have investigated age-related retinal tissue loss with OCT, 4851 to the best of our knowledge this is the first investigation that not only analyzed the gridwise GCL thickness changes but also clustered them into statistically separable theme classes according to temporal regression signatures. This study demonstrated that pattern recognition can be applied to retinal thickness measurement, with the advantage of allowing a large number of data points to be analyzed for multiobjective optimization over n dimensions and, at the same time, statistically test the separability of the clusters.…”
Section: Discussionmentioning
confidence: 99%